Overexpression or Deletion of Ergosterol Biosynthesis Genes Alters Doubling Time, Response to Stress Agents, and Drug Susceptibility in Saccharomyces cerevisiae - Somanon Bhattacharya (American Society for Microbiology, 2018)
ABSTRACT Ergosterol (ERG) is a critical sterol in the cell membranes of fungi, and its biosynthesis is tightly regulated by 25 known enzymes along the ERG production pathway. The effects of changes in expression of each ERG biosynthesis enzyme in Saccharomyces cerevisiae were analyzed by the use of gene deletion or plasmid-borne overexpression constructs. The strains overexpressing the ERG pathway genes were examined for changes in doubling time and responses to a variety of stress agents. In addition, ERG gene overexpression strains and ERG gene deletion strains were tested for alterations in antifungal drug susceptibility. The data show that disruptions in ergosterol biosynthesis regulation can affect a diverse set of cellular processes and can cause numerous phenotypic effects. Some of the phenotypes observed include dramatic increases in doubling times, respiratory deficiencies on glycerol media, cell wall insufficiencies on Congo red media, and disrupted ion homeostasis under iron or calcium starvation conditions. Overexpression or deletion of specific enzymes in the ERG pathway causes altered susceptibilities to a variety of classes of antifungal ergosterol inhibitors, including fluconazole, fenpropimorph, lovastatin, nystatin, amphotericin B, and terbinafine. This analysis of the effect of perturbations to the ERG pathway caused by systematic overexpression of each of the ERG pathway genes contributes significantly to the understanding of the ergosterol biosynthetic pathway and its relationship to stress response and basic biological processes. The data indicate that precise regulation of ERG genes is essential for cellular homeostasis and identify several ERG genes that could be exploited in future antifungal development efforts. IMPORTANCE A common target of antifungal drug treatment is the fungal ergosterol biosynthesis pathway. This report helps to identify ergosterol biosynthesis enzymes that have not previously been appreciated as drug targets. The effects of overexpression of each of the 25 ERG genes in S. cerevisiae were analyzed in the presence of six stress agents that target essential cellular processes (cell wall biosynthesis, protein translation, respiration, osmotic/ionic stress, and iron and calcium homeostasis), as well as six antifungal inhibitors that target ergosterol biosynthesis. The importance of identifying cell perturbations caused by gene overexpression or deletion is emphasized by the prevalence of gene expression alterations in many pathogenic and drug-resistant clinical isolates. Genes whose altered expression causes the most extensive phenotypic alterations in the presence of stressors or inhibitors have the potential to be drug targets.